Kinerja Pegawai Dalam Peningkatan Kualitas Pelayanan Adiministrasi Kependudukan di Kantor Camat Ongka Malino Kabupaten Parigi Moutong - Sopia, Siti; Tahir, Arifin; Mozin, Sri Yulianty (Socius: Jurnal Penelitian Ilmu-Ilmu Sosial, 2025)
This study aims to analyze the effect of employee performance on the quality of public administrative services at the Ongka Malino Sub-District Office, Parigi Moutong Regency. Using a quantitative method with a descriptive approach, data were collected through questionnaires completed by 30 respondents. The results show that employee performance has a positive and significant effect on the quality of public services, with a significance value of 0.000 0.05 and a t-value of 7.305 t-table value of 0.0018. The coefficient of determination (R²) of 65,6% indicates that employee performance contributes to improving the quality of public services, while the remaining 34,4% is influenced by other factors. To maintain and improve service quality, it is recommended that the sub-district office enhance employee competencies through training, improve internal communication, and implement a more structured performance evaluation system.